1978
DOI: 10.1056/nejm197804272981703
|View full text |Cite
|
Sign up to set email alerts
|

Normal Chest Roentgenograms in Chronic Diffuse Infiltrative Lung Disease

Abstract: We undertook this study to determine the prevalence of normal roentgenograms in chronic diffuse infiltrative lung diseases. Of 458 patients with such disorders histologically confirmed, 44, or 9.6 per cent, had normal pre-biopsy films. In this group with normal x-ray films, desquamative interstitial pneumonia, sarcoidosis and allergic alveolitis were the most frequent diagnoses. Dyspnea was the principal complaint, and fine rales were common. The vital capacity was reduced in 57 per cent, and the single-breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
7

Year Published

1979
1979
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(109 citation statements)
references
References 25 publications
3
97
0
7
Order By: Relevance
“…Reports of the distribution of pulmonary shadowing in farmer's lung are inconsistent [22]. In hypersensitivity pneumonitis, chest radiographic findings may be normal [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the distribution of pulmonary shadowing in farmer's lung are inconsistent [22]. In hypersensitivity pneumonitis, chest radiographic findings may be normal [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…He also believes that experts agree routinely about the interpretation of normal fi lms. However, Epler et al (20) reported that in a number of subjects with apparently normal fi lms, subsequent biopsies confi rmed chronic diffuse infi ltrative lung disease. Frumkin et al (21) also found a considerable inter-reader variability.…”
Section: Resultsmentioning
confidence: 99%
“…HRCT may identify diffuse parenchymal disease undetectable on plain x-ray. In one large series, approximately 10 % of patients with biopsy-proven diffuse lung disease had an apparently normal chest radiograph [21]. In some cases, appearances on HRCT are pathognomonic of a histo-specific diagnosis: typical HRCT patterns are listed in Table 2.…”
Section: High Resolution Computed Tomographymentioning
confidence: 99%